Incarceration of Iodine in a Pyrene‐Based Metal–Organic Framework. Issue 2 (11th December 2018) - Gładysiak, Andrzej; Nguyen, Tu N.; Spodaryk, Mariana; Lee, Jung‐Hoon; Neaton, Jeffrey B.; Züttel, Andreas; Stylianou, Kyriakos C.
Abstract: A pyrene‐based metal‐organic framework (MOF)SION‐8 captured iodine (I2 ) vapor with a capacity of 460 and 250 mg g −1 MOF at room temperature and 75 °C, respectively. Single‐crystal X‐ray diffraction analysis and van‐der‐Waals‐corrected density functional theory calculations confirmed the presence of I2 molecules within the pores ofSION‐8 and their interaction with the pyrene‐based ligands. The I2 –pyrene interactions in the I2 ‐loadedSION‐8 led to a 10 4 ‐fold increase of its electrical conductivity compared to the bareSION‐8 . Upon adsorption, ≥95 % of I2 molecules were incarcerated and could not be washed out, signifying the potential ofSION‐8 towards the permanent capture of radioactive I2 at room temperature. Abstract : Trapped forever ! A pyrene‐based MOF, SION‐8, efficiently adsorbs vapor iodine, however, unlike in other known materials, this capture is permanent at room temperature. The formation of the stable charge‐transfer complexSION‐8⊃I2 can be tracked with conspicuous color and electrical conductivity changes.